Evaluation and Selection of Multilocus Variable-Number Tandem-Repeat Analysis Primers for Genotyping Brucella abortus Biovar 1 Isolated from Human Patients - Lee, Subok (2013)
OBJECTIVES: Brucellosis is the most common bacterial zoonosis in the world. Multilocus variable-number tandem-repeat (VNTR) analysis (MLVA) is a molecular method for genotyping bacterial species. Brucella abortus biovar I was isolated from most of the brucellosis-suspected patients in Korea. This study was conducted to investigate the ability of various MLVA primers that are used for molecular typing B. abortus isolates and for analyzing their epidemiological data. METHODS: A total of 80 human isolates of B. abortus biovar I isolated from human patients and the reference strain were used for MLVA. Genetic diversity was determined by calculating the Simpson's diversity index (DI) of each VNTR locus. The Brucella strains were subcultured 30 times to determine the stability of each locus. The DNA of the strains cultivated in each passage was extracted and subjected to MLVA for further investigation. RESULTS: The 15 VNTR loci were selected based on high DI values. The DIs of the 15 VNTR loci showed considerable discrimination power ranging from 59% for Bruce 43 to 87% for Bruce 22. Bruce 09, Bruce 11, Bruce 16, Bruce 42, and Bruce 43 were confirmed to remain stable in vitro among the 15 VNTR loci selected. CONCLUSION: The results of this study suggest that the five loci subsets may be a useful epidemiological tool for investigating B. abortus biovar 1 outbreak.